Global tastes, local choices: Strontium isotope and concentration evidence for changing dietary input in Roman Nijmegen, the Netherlands - Maura De Coster; Joep Hendriks; Hannah F. James; Christophe Snoeck; Gareth R. Davies; Lisette M. Kootker (PLoS ONE, 2026)
This study investigates dietary practices and local interaction in Roman and pre-Roman Nijmegen, the Netherlands, through strontium isotope ratios (⁸⁷Sr/⁸⁶Sr) and concentration measurements on cremated human remains from rural, urban, and military contexts, which primarily reflect the geological provenance of dietary strontium. Located along the Lower Rhine borderlands, Nijmegen formed a key node within the Batavian region, where local communities intersected with imperial networks. The results reveal isotopic contrasts between site types: urban and military groups tend to display higher strontium concentrations, possibly consistent with greater engagement with salt-preserved and salt-rich foods, while in the northern contexts relatively stable concentrations alongside a narrowing of isotope ratios may suggest continuity in dietary practices, potentially including earlier traditions of salt consumption. These patterns indicate that dietary change was not uniform, but shaped by the interaction between emerging imperial foodways and pre-existing local practices. Rather than reflecting simple differences in access, the isotopic evidence points to varied and context-dependent forms of engagement with Roman provisioning systems.